Volume 5: Structures and Dynamics, Parts a and B 2008
DOI: 10.1115/gt2008-50862
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations of Friction Rings Damping of Blisks

Abstract: The use of friction ring dampers for integrally bladed disks (blisks) is investigated numerically and experimentally in this paper. A test rig was developed and consists in an industrial HP compressor blisk rotating inside a vacuum chamber. Excitation is produced through piezoelectric actuators and measured data are obtained from strain gauges. Non-linear resonance curves obtained by stepped sine tests are studied. Interesting phenomena on the behaviour of this damping technology are obtained experimentally. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Therefore the friction damping concept has been frequently applied in turbomachinery applications and various research works for analyzing the dynamic characteristics of structures with friction joints have been undertaken. For example we can mention researches on structures with underplatform dampers [15][16][17][18][19], approach for characterizing the dynamic behavior of a friction damper [20], shrouds with a frictional interface to reduce the dynamic stresses in turbine blades via the comparison between measured and calculated frequency response functions for bending and torsional vibrations of the blade [21], optimization of interblade friction damper design with respect to an optimal damper geometry and damper mass [22], impact of friction in blade with root joints [23] or friction rings [24]. More generally, the review papers of Gaul and Nitsche [25] and Feeny et al [26] provided also a historical overview of structural and mechanical systems on the general topic of friction damping.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the friction damping concept has been frequently applied in turbomachinery applications and various research works for analyzing the dynamic characteristics of structures with friction joints have been undertaken. For example we can mention researches on structures with underplatform dampers [15][16][17][18][19], approach for characterizing the dynamic behavior of a friction damper [20], shrouds with a frictional interface to reduce the dynamic stresses in turbine blades via the comparison between measured and calculated frequency response functions for bending and torsional vibrations of the blade [21], optimization of interblade friction damper design with respect to an optimal damper geometry and damper mass [22], impact of friction in blade with root joints [23] or friction rings [24]. More generally, the review papers of Gaul and Nitsche [25] and Feeny et al [26] provided also a historical overview of structural and mechanical systems on the general topic of friction damping.…”
Section: Introductionmentioning
confidence: 99%
“…Summing up all damping forces that act on the moving parts (5) í 2 (6) all terms of mixed fields (ßi B2) cancel out as they only contribute to separating forces between copper plate and magnet assembled in one half of the damping element. Taking the rotational symmetry and the geometric dimensions depicted in Fig.…”
Section: (4)mentioning
confidence: 98%
“…In this approach, vibration amplitude reduction is obtained through energy dissipation in friction contacts. Besides blade-to-blade [2] or blade-to-root [3] contact, a broad variety of coupling devices such as underplatform dampers [4,5], lacing wires and friction rings [6] have been studied in great detail during the last couple of years. To include those friction forces in vibration analyses, sophisticated contact models are necessary [7,8], most of them containing parameters that are difficult to estimate, such as contact stiffness [9] and friction coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…More recent research shows the ease of AFT schemes in handling nonlinearities due to friction force as well as the harmonic features of the excitation. Liu et al (2010a) showed the application of the AFT method in vibration analysis of shrouded blade systems, Laxalde et al (2008) showed bladed discs with friction ring dampers, Leib et al (2008) showed the efficiency of the AFT schemes over time-domain techniques in their investigation of two overlaying beams under harmonic vibrations over a very large range of frequency. Liu et al (2010b) introduced a fast anti-alias Fourier transform as an extension to the AFT method to improve the accuracy of the calculation.…”
Section: Modelling Of Frictionally Damped Systemsmentioning
confidence: 99%
“…This assumption does not always depict the true physical phenomenon, for example, for tangential loads, where sliding must exist at the friction interface, leading to energy dissipation and damping. Laxalde et al (2008) used Dahl's model to investigate the use of friction ring dampers in bladed discs. Canudas et al (1995) proposed a model that combines all threeStribeck, Dahl and Dankowicz models.…”
Section: Introductionmentioning
confidence: 99%